ChemiTEM – Transmission Electron Microscopy Optimized for Chemistry and Material Science. Issue 9 (2nd September 2021) - Hetaba, Walid; Imlau, Robert; Duarte‐Correa, Liseth; Lamoth, Maximilian; Kujawa, Stephan; Lunkenbein, Thomas
Abstract: Invited for this month's cover is the group of Walid Hetaba and Thomas Lunkenbein at the Max‐Planck‐Institutes in Berlin and Mülheim (Germany). The cover picture shows the ChemiTEM acquisition workflow in a tablet app in front of a transmission electron microscope (TEM). Additionally, the results obtained by a TEM‐expert and by non‐expert TEM users are shown left and right of the microscope, respectively. It symbolises that using the ChemiTEM workflows, non‐expert TEM users can proficiently use a TEM and generate data which is of comparable quality as the data obtained by a TEM‐expert. Furthermore, the training time of the users is reduced and electron microscopical investigations can be performed with much higher efficiency. ChemiTEM extends the TEM user base and makes this instrument a versatile standard lab tool. Read the full text of their Full Paper at 10.1002/cmtd.202100001 . Abstract : "… It was quite exciting to see how fast non‐experts can learn to proficiently use electron microscopes and how much easier it makes the job of the teacher during TEM training sessions… " Find out more about the story behind the front cover research at 10.1002/cmtd.202100001 .